(untitled) (Italian Journal of Public Health, 2009)
Background: In the last decades, there has been increased worldwide interest in the management of health risks from indoor radon. Methods: From 2006 to 2008, a survey on air radon levels was carried out in a total of 57 indoor gymnasia respectively located in the urban area of Palermo (Sicily) and Sassari (Sardinia). Results: The indoor radon levels were generally low with different geometric means in the two geographic areas (14.3 Bq/m3 in Palermo and 36 Bq/m3 in Sassari, respectively). Overall, in both groups increasing values of radon were found during the night and the early morning, with radon concentrations significantly lower during working time than at other times. The analysis of structural parameters showed that direct contact with the soil significantly correlated with increased levels of radon in gymnasia located in Palermo’s area (p<0.05). Furthermore, higher radon levels in Sicilian structures were also associated, although not significantly, with lack of sumps (19.3 vs 12.9 Bq/m3), location below the ground level (18.8 vs 8.7 Bq/m3), lack of windows (25 vs 13.2 Bq/m3), presence of forced ventilation (15.5 vs 7.3 Bq/m3) and with cracks or moisture tracks (15.7 vs 13.2 Bq/m3). Conclusions: Radon tends to accumulate in indoor sites and it’s monitoring, especially in buildings with potentially overcrowded conditions, could be of public health interest. Mitigation measures and minimization of the number of structural and functional risk parameters should be strongly encouraged in order to limit radon accumulation especially in countries with higher radium concentration in the soil.